Fashion product design and design practices in the circular economy: sustainability and material culture in everyday consumption (Revista de Ensino em Artes, Moda e Design, 2025)
The fashion industry faces a severe environmental crisis, and the sustainable solutions adopted remain superficial in the face of a linear production model. The circular economy emerges as a promising alternative, but its practical implementation remains limited. Therefore, this research aimed to investigate how Design for Disassembly (DfD), as a design strategy, can be understood as a sociomaterial practice that reconfigures sustainable fashion consumption, based on the framework of Practice Theories. To this end, the methodology adopted was theoretical-conceptual research and a qualitative approach, through a critical literature review, which identified, via interpretive reading, convergences, tensions, and conceptual gaps among the authors. Thus, the research results can be categorized into a six-axis sociomaterial matrix: design materiality, involved competencies, attributed meanings, design practice as social practice, circularity as a social structure, and barriers to adoption. The findings indicate that DfD should be understood not only as a technical solution but as a situated practice, activated by interactions between materials, knowledge, and cultural meanings. Its viability depends on social appropriation and the re-signification of production and consumption routines.
Keywords: circular economy; product design; sustainability; consumption